Learning Cycle Model as a Strategy for Improving Science Learning Outcomes in Elementary Schools (Edukasi, 2022)
This study aims to improve the learning outcomes of science students in elementary schools using the Learning Cycle model. This study uses several scientific journals as references in their compilation. This research was conducted based on reviews from scientific journals, data or information from the internet and collections of national and international journals. The author uses the Learning Cycle model as a strategy to increase the activeness of students in the learning process to communicate the results of their thoughts. So that in science learning it makes students active, creative, innovative and responsible. In the implementation of teaching and learning, learning is very important to be used as a benchmark. Prediction of research results using the Learning Cycle model is expected that students can improve science learning outcomes in cognitive, affective and psychomotor aspects.